2012
DOI: 10.1371/journal.pone.0040798
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved Reticulocytes Derived from Hematopoietic Stem Cells Can Be Invaded by Cryopreserved Plasmodium vivax Isolates

Abstract: The development of a system for the continuous culture of Plasmodium vivax in vitro would benefit from the use of reticulocytes derived from differentiated hematopoietic stem cells (HCS). At present, the need to use both fresh reticulocytes and fresh P. vivax isolates represents a major obstacle towards this goal, particularly for laboratories located in non-endemic countries. Here, we describe a new method for the cryopreservation of HSC-derived reticulocytes to be used for both P. falciparum and P. vivax inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 29 publications
1
44
0
2
Order By: Relevance
“…Hypotonic lysis resulted in substantial reduction of the neonatal CD71 + CD235a + cells (85% reduction, Figure 4B). These results are in stark contrast to the stability of murine neonatal CD71 + erythroid splenocytes to hypotonic lysis (19% reduction, data not shown) and suggest that these cells are predominantly reticulocytes(23, 24). FACS-enrichment of the neonatal human CD71 + CD235a + cells with cytospin examination after Wright’s stain or methylene blue confirmed that these cells were predominantly enucleated reticulocytes (Figure 4A).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Hypotonic lysis resulted in substantial reduction of the neonatal CD71 + CD235a + cells (85% reduction, Figure 4B). These results are in stark contrast to the stability of murine neonatal CD71 + erythroid splenocytes to hypotonic lysis (19% reduction, data not shown) and suggest that these cells are predominantly reticulocytes(23, 24). FACS-enrichment of the neonatal human CD71 + CD235a + cells with cytospin examination after Wright’s stain or methylene blue confirmed that these cells were predominantly enucleated reticulocytes (Figure 4A).…”
Section: Resultsmentioning
confidence: 61%
“…The mononuclear fraction from healthy human cord blood contains a large population of nucleated red blood cells (nRBCs) and reticulocytes [both express CD71 and CD235a](8, 23, 24). Similar to the immunosuppressive function by neonatal murine CD71 + erythroid splenocytes, human cord blood CD71 + erythroid cells can inhibit TNF-α production ex vivo(8).…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability to derive reticulocytes that can be infected by P. vivax from haematopoietic stem cells in vitro suggests that this may one day be possible 144 . So far, the related non-human primate parasites Plasmodium cynomolgi and Plasmodium knowlesi have been used to gain insight into P. vivax-like biology.…”
Section: Box 3 | Gaining Insight Into Plasmodium Vivax-like Biologymentioning
confidence: 99%
“…One advantage of HSCs is that the asynchronous maturation of the erythroid cells enables continuous production of fresh reticulocytes that have already been shown as suitable target cells for P. vivax invasion. [86][87][88][89] Finally, latest recent report from Van et al 88 shows that CD34z-enriched populations of UCB produced the highest amount of reticulocytes, and these cells can be invaded by P. vivax. Van et al also provide proof that P. vivax parasites have a preference for invading immature reticulocytes, which reduces further the panel of blood cells available for infection and therefore increases the technical difficulty of P. vivax bloodstage cultures.…”
Section: Source Of Sporozoitesmentioning
confidence: 99%
“…The cost, the technical difficulty, labour intensity and for some countries the need for special authorisations could make methods that rely on HSC-derived reticulocytes less accessible. In this regard, the results obtained by Noulin et al 87 showing that it is possible to cryopreserve P. vivax infected HSC-derived reticulocytes introduces the possibility of creating stocks of reticulocytes to use as target cells for the establishment of an in vitro culture of P. vivax. Some recent work focuses on the development of cell lines, either from erythroleukemia (for review, see Ref.…”
Section: Source Of Sporozoitesmentioning
confidence: 99%